The interactions of working children and adolescents in the streets of Xalapa, Veracruz, Mexico: analysis of control mechanisms and strategies of resistance - Narváez Aguilera, Arturo (2019)
To analyze the interactions of working children and adolescents in the streets of Xalapa, Veracruz, Mexico, from a sociological perspective, the categories of the control mechanisms and the production of resistance strategies are addressed, as conceptual foundations to explain the permanent tension between the child labor action and the existence of a regime of control and regulation of child labor. First, it exposes the operation of devices and control devices at various scales, which move from the threshold of a normative and hegemonic vision in a neoliberal key of the public space, to the protectionist-tutelares typical of the modern conception of childhood. Second, a conceptualization of the resistances observed in the interaction system of working children and adolescents is established. Third, the meanings that the street and its economic activity have for social subjects are described. Finally, the collective practices of resistance are explained, from the notion of social actors for survival.